The loss of macular ganglion cells begins from the early stages of disease and correlates with brain atrophy in multiple sclerosis patients. (January 2019) - Pietroboni, Anna M; Dell'Arti, Laura; Caprioli, Michela; Scarioni, Marta; Carandini, Tiziana; Arighi, Andrea; Ghezzi, Laura; Fumagalli, Giorgio G; De Riz, Milena A; Basilico, Paola; Colombi, Annalisa; Benatti, Eleonora; et al.
Background: The importance of neurodegeneration in multiple sclerosis (MS) is increasingly well recognized. Objectives: To evaluate retinal pathology using optical coherence tomography (OCT) and to investigate possible associations between retinal layers' thickness and specific patterns of gray matter volume in patients with a new diagnosis of MS. Methods: A total of 31 patients underwent OCT scans and brain magnetic resonance imaging. In total, 30 controls underwent the same OCT procedure. The association between focal cortical volume and OCT measurements was investigated with voxel-based morphometry (VBM). Results: Compared to controls, patients' macular retinal nerve fiber layer (mRNFL), macular ganglion cell layer (mGCL), macular inner plexiform layer (mIPL), and macular ganglion cell-inner plexiform layer (mGCIPL) thickness were significantly reduced ( p = 0.0009, p = 0.0003, p = 0.0049, and p = 0.0007, respectively). Peripapillary RNFL (pRNFL) and temporal sector pRNFL (T-pRNFL) did not show any significant changes, although there was a trend toward T-pRNFL thinning ( p = 0.0254). VBM analysis showed that mGCIPL and pRNFL were significantly correlated with the volume reduction of occipital-parietal cortex ( p < 0.005). Conclusion: mRNFL, mGCL, and mIPL are significantly reduced in MS patients without concomitant pRNFL thinning. These retinal changes show a significant association with cortical regions that are known to be important for visuospatial performance.